PENGARUH EFFLEURAGE MASSAGE TERHADAP NYERI PUNGGUNG PADA IBU HAMIL DI PMB ROSITA KOTA PEKANBARU - Kiki Megasari; Yulrina Ardhiyanti; Widya Juliarti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Discomfort in the third trimester experienced by pregnant women, such as back pain, can occur due to hormonal changes, including an increase in the hormone relaxin, which causes the pelvic bones to loosen and it can lead to the tension in the back and thighs muscles which increasing the risk of pain. The management of back pain in pregnant women includes pharmacological approaches using analgesic drugs and non-pharmacological methods, such as effleurage massage therapy which can reduce back pain in pregnant women, alleviate muscle tension, improve mobility, and enhance blood circulation. The objective of this research is to investigate the effect of effleurage massage on the reduction on back pain in third trimester pregnant women at PMB Rosita Pekanbaru. The research was conducted from July 20th to August 6th, 2025, employing an experimental research with a pre-experimental design utilizing pretest and posttest design. The population of this study consisted of all third trimester pregnant women receiving prenatal care at PMB Rosita. The sample of this research was 15 pregnant women selected through purposive sampling. Data collection involved observation, with the research instrument employing observation sheets. The research findings indicated that the average back pain in third trimester pregnant women before the intervention was mostly moderate (5.60), while after the intervention, it was predominantly mild (2.26). The Wilcoxon signed-rank test, with a 95% confidence level, yielded a p-value of 0.001, indicating a significant effect of effleurage massage on reducing back pain. It is recommended that PMB Rosita consider implementing effleurage massage as a non-pharmacological treatment alternative for third trimester pregnant women experiencing back pain.Keywords: Back Pain, Third Trimester Pregnant Women, Effleurage Massage